Dasar Pertimbangan Putusan-Putusan Kasasi Hakim Agung Artidjo Alkostar terhadap Kasus Korupsi Tahun 2013-2015 - Ahmad & Ari Bahiej & Arifin (UIN Sunan Kalijaga Yogyakarta, 2016)
The results of this study concluded that the Justice Artidjo Alkostar in implementing the article in the Supreme Court is to first look at the elements of criminal acts committed by the defendant. Elements of crime have been met is then adjusted with a passage that has been indicted. In such adjustment, Chief Justice Artidjo Alkostar using grammatical interpretation. Besides the Chief Justice makes Artidjo Alkostar defendant who use public office (political corruption) to commit criminal acts of corruption as a consideration in aggravate the punishment for corruption (zero tolerance or a zero tolerance). But Justice Artidjo Alkostar in imposing a sentence that is still to include the spirit of fighting corruption and not applying the spirit of deciding a case with the fairest and faith not merely to convict.